MODERN PREVENTIVE METHODS FOR OSTEOCHONDROSIS - Normurodov Jahongir (JOURNAL OF NEW CENTURY INNOVATIONS, 2025)
Abstract: Today, many people are forced to work in the same position for a long time. Diseases associated with the spine, in particular osteochondrosis, are widespread among office workers, computer workers, and those who lead a sedentary lifestyle. This disease causes changes in the spinal discs and bone structures, which reduces the quality of a person’s life. However, in modern conditions, there are effective preventive measures to prevent osteochondrosis. In this article, we will talk about methods that prevent the development of the disease and ways to form a healthy lifestyle.